y=3
y^3(y^3-y)=
3^3(3^3-3)=
27(27-3)=
27(24)=648
72
Neither y3x-3 nor 3x-y3 are equations, and so neither of them can have a solution. Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
6y-y3 = 3
14 minus -3 is 17
-8
72
y3 x y3 - y (3)3 x 3(3) - 3 9 x 9 - 3 = ? 9 x 9= 81 81 - 3 = 78 I hope that solves your problem
If a equals 3 and b equals minus 5 then a minus b equals what
Neither y3x-3 nor 3x-y3 are equations, and so neither of them can have a solution. Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
(-3)-(4)=(-3)+4=1 Minus times minus equals plus. The reason for this we need not discuss.
6y-y3 = 3
14 minus -3 is 17
-7
-8
18
7-3=4
so, if 2 minus Ln times 3 minus x equals 0, then 2 minus Ln times 3 equals x, therefore 2 minus Ln equals x divided by three, so Ln + X/3 = 2 therefore, (Ln + [X/3]) = 1